THE MYSTERY OF BUDGET ABSORPTION AT SKPD “BIRU DAUN” - Akhmad Jauhari; Tarjo Tarjo; Bambang Haryadi (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
The purpose of this study is to know the budget absorption at SKPD “Biru Daun” which was still below 80% until the end of the 2014 fiscal year. This study uses qualitative method with case study approach. Data collection techniques are carried out through interviews, observation and documentation. Data analysis techniques used consist of data collection, data reduction, data presentation and conclusions. Data validation is done by triangulation method. The results of the study show that there are many irregularities in budget planning, such as the intervention of policy makers, delays in the implementation of auctions, tender committees that are not transparent, and budget accountability that does not use computer technology.